The Extent of Inclusion of STEM Approach Criteria in the Developed Physics Textbooks for Secondary Stage in Jordan - Malkawi, Amal; AL-Yousef, Ebrahim (Jordan Journal of Educational Sciences, 2019)
This study aimed at investigating the extent of inclusion of STEM approach criteria in the content of developed physics textbooks for secondary stage in Jordan. The sample of the study consisted of the first four chapters from both of the developed physics textbooks for the first and second secondary grades. The study used the analytical descriptive method , by using the content analysis method which consisted of (30) indicators , distributed into (7) main domains. The reliability of the tool was checked by using Holsti Formula , and the reliability of the analysis was calculated by using Kappa Formula. The results of the study indicated that there was a decline in the inclusion level of STEM approach criteria in the developed physics textbooks content. The percentage of inclusion of STEM criteria was about (36%) in the both textbooks. There was a difference in inclusion percentages of both books in the tool's domains. The “Apply technology strategically” criterion has the lowest percentage of inclusion in the textbook for first secondary grade , while the “collaborate as a STEM team” criterion has the highest percentage in the same book. The percentage of the “engage in inquiry” criterion has the lowest percentage of inclusion in the book for second secondary class , while the highest was the “collaborate as a STEM team” criterion in the same textbook